Primary Ciliary Signaling in the Skin—Contribution to Wound Healing and Scarring - Hosio, Mayu; Jaks, Viljar; Lagus, Heli; Vuola, Jyrki; Ogawa, Rei; Kankuri, Esko (Frontiers in Cell and Developmental Biology, 2020)
Primary cilia (PC) are solitary, post-mitotic, microtubule-based, and membrane-covered protrusions that are found on almost every mammalian cell. PC are specialized cellular sensory organelles that transmit environmental information to the cell. Signaling through PC is involved in the regulation of a variety of cellular processes, including proliferation, differentiation, and migration. Conversely, defective, or abnormal PC signaling can contribute to the development of various pathological conditions. Our knowledge of the role of PC in organ development and function is largely based on ciliopathies, a family of genetic disorders with mutations affecting the structure and function of PC. In this review, we focus on the role of PC in their major signaling pathways active in skin cells, and their contribution to wound healing and scarring. To provide comprehensive insights into the current understanding of PC functions, we have collected data available in the literature, including evidence across cell types, tissues, and animal species. We conclude that PC are underappreciated subcellular organelles that significantly contribute to both physiological and pathological processes of the skin development and wound healing. Thus, PC assembly and disassembly and PC signaling may serve as attractive targets for antifibrotic and antiscarring therapies.